(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Dark adaptation ability is one of visual function which has an association with eyes ability to recover after receiving a light exposure in a certain time (Sommer, 1982). Udomkesmalee et. al (1992) stated that zinc supplementation gives a significant effect on dark adaptation ability in children. Furthermore, a finding has been found by Christian et. al. (2001) who revealed that deficiency of zinc could contribute to night blindness, an early symptom of vitamin A deficiency. Objectives. This study is to explain the relationship between zinc deficiency and vitamin A toward dark adaptation ability in primary school children in Deras village, Kedungjati, Grobogan district. Methods. Observational study design by using cross-sectionals approach was utilized in this project. The total sample was 51 primary school children in years five at Deras primary school 1 and 2. Data collection was taken by health professionals including general practitioners, ophthalmologist, nutritionist, and nurses. Data analysis used SPSS program to describe the findings. Dark Adaptation Ability was measured by using a Photostress test method. Blood sampling was used to determine zinc and retinol status, and dietary survey was done to determine zinc and vitamin A intake per day. To test the study hypothesizes, a logistic regression was used. The significant level was set at 95%. Results. One of five primary school children (21.6%) has a lower level of dark adaptation ability (< 50 seconds). Whereas, 33.3% (n=17) of sample experienced zinc deficiency and 15.7% (n=8) suffer from vitamin A deficiency, based on blood serum examination. zinc intake is less by only 0.7 mg per day. The study showed that zinc and vitamin A deficiency are risk factors to Dark Adaptation Ability in preschool children (prevalence ratio = 21.6 and 45.9). Conclusion. Using a Logistic regression model was found that there will be an improvement of odds dark adaptation ability as 21,6 times in the children without zinc deficiency compared to the children with zinc deficiency, and 45,9 times in the children with adequately vitamin A rather than the children who experienced inadequately Vitamin A.